IMPLEMENTATION OF THE PENTAHELIX MODEL AS A FOUNDATION FOR DEVELOPING TOURISM POTENTIAL IN MAJALENGKA REGENCY - Rizki Nurul Nugraha; Nada Widya Candra Nurani (Jurnal Inovasi Penelitian, 2022)
The concept of tourism development with the Pentahelix model is often found to analyze in the economic sector, in fact the Petahelix Model of Cooperation of Academics, Business, Community, Government and Media, which called ABCGM, is very important in tourism development because it covers all parties also because it can provide benefits and benefits for society and the environment there good integration so as to create activities, facilities, services, and quality tourism experience and value benefits. This research uses a descriptive qualitative approach. Where this research method uses literature studies, namely studies carried out by identifying, formulating, and setting goals and benefits using literature review studies. The purpose of this study is to find out how the Pentahelix model can be used to develop tourism potential in Majalengka Regency. The results can be seen if the Pentahelix model can be one of the strategies that if optimal its implementation will provide welfare for all parties.